The 18S rRNA m6A methyltransferase METTL5 promotes mouse embryonic stem cell differentiation. (11th August 2020) - Xing, Ming; Liu, Qi; Mao, Cong; Zeng, Hanyi; Zhang, Xin; Zhao, Shuqin; Chen, Li; Liu, Mingxi; Shen, Bin; Guo, Xuejiang; Ma, Honghui; Chen, Hao; et al.
Abstract: RNA modifications represent a novel layer of regulation of gene expression. Functional experiments revealed that N 6 ‐methyladenosine (m 6 A) on messenger RNA (mRNA) plays critical roles in cell fate determination and development. m 6 A mark also resides in the decoding center of 18S ribosomal RNA (rRNA); however, the biological function of m 6 A on 18S rRNA is still poorly understood. Here, we report that methyltransferase‐like 5 (METTL5) methylates 18S rRNA both in vivo and in vitro, which is consistent with previous reports. Deletion of Mettl5 causes a dramatic differentiation defect in mouse embryonic stem cells (mESCs). Mechanistically, the m 6 A deposited by METTL5 is involved in regulating the efficient translation of F‐box and WD repeat domain‐containing 7 (FBXW7), a key regulator of cell differentiation. Deficiency of METTL5 reduces FBXW7 levels and leads to the accumulation of its substrate c‐MYC, thereby delaying the onset of mESC differentiation. Our study uncovers an important role of METTL5‐mediated 18S m 6 A in mESC differentiation through translation regulation and provides new insight into the functional significance of rRNA m 6 A. Synopsis: METTL5, the m6A methyltransferase for 18S rRNA, is critical for Fbxw7 translation and mESC differentiation. METTL5 is dispensable for mESC pluripotency. Orderly differentiation of mESCs requires METTL5. METTL5 promotes the translation efficiency of Fbxw7. Abstract : METTL5, the m6A methyltransferase for 18S rRNA, is critical for Fbxw7 translation and mESC differentiation.